2020
DOI: 10.3390/microorganisms8020194
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans and Actinomyces naeslundii Interaction in Dual-Species Biofilm

Abstract: The study of bacterial interaction between Streptococcus mutans and Actinomyces naeslundii may disclose important features of biofilm interspecies relationships. The aim of this study was to characterize—with an emphasis on biofilm formation and composition and metabolic activity—single- and dual-species biofilms of S. mutans or A. naeslundii, and to use a drip flow reactor (DFR) to evaluate biofilm stress responses to 0.2% chlorhexidine diacetate (CHX). Single- and dual-species biofilms were grown for 24 h. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 68 publications
(96 reference statements)
0
16
0
Order By: Relevance
“…Consistent with reported studies, we also found that A. johnsonii was enriched in the healthy controls. de Oliveira RVD reported that A. johnsonii is capable of increasing local pH by producing ammonia and alkali and can lead to a decrease in lactic acid production when interacting with S. mutans ( de Oliveira et al, 2020 ). Our results suggest that C. hominis was enriched in caries-free adolescents and that its connections with caries have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with reported studies, we also found that A. johnsonii was enriched in the healthy controls. de Oliveira RVD reported that A. johnsonii is capable of increasing local pH by producing ammonia and alkali and can lead to a decrease in lactic acid production when interacting with S. mutans ( de Oliveira et al, 2020 ). Our results suggest that C. hominis was enriched in caries-free adolescents and that its connections with caries have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, vital for the long-term sustainability of additively manufactured titanium devices to protect the surface against bacterial contamination. Among other species present in the oral cavity, Streptococcus mutans and Lactobacillus rhamnosus are especially important due to their ability to release lactic acid, decrease the pH, and survive in acidic environments, thereby becoming dominant corrosive microorganisms [29][30][31][32][33][34][35][36]. In addition to bacteria, it is worth mentioning Candida albicans, because of its symbiotic relations with S. mutans under biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to bacteria, it is worth mentioning Candida albicans, because of its symbiotic relations with S. mutans under biofilm formation. This leads to increased glucan production, enhanced adherence, and increased biofilm complexity amplifying their harmful effect and hinders the effectiveness of antimicrobial substances [29,[33][34][35][36]. Therefore, these five species of microorganisms have been chosen in this study of biofilm formation on the 3D-printed raw fixation plates.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that Actinomyces spp. play an essential role in the formation of dental biofilms and could contribute to the development of diseases such as caries and periodontitis ( de Oliveira et al., 2020 ). Dioguardi et al.…”
Section: Discussionmentioning
confidence: 99%